The nurse’s role in caring for women victims of sexual violence in the emergency department (Research, Society and Development, 2023)
This study aims to analyze the nursing care provided to women victims of sexual violence in the emergency room. It has a descriptive character and a qualitative approach. Data collection was carried out through bibliographic research, produced through articles available in the databases Lilacs (Latin American and Caribbean Literature in Health Sciences), SciELO (Scientific Electronic Library Online), BVS (Virtual Library in Health), BDENF (Nursing Database) and Google Scholar. Fifteen articles were selected that responded to the research objective, published in the period from 2012 to 2021. The selected authors agree on the importance of nursing care in this scenario, that care is offered in a humanized and comprehensive way, prioritizing qualified listening and procedures that minimize the damage caused by aggression. There were failures in nursing care for women victims of sexual violence, and there was a need for training nurses working in the emergency room.